Agonist triggering in oocyte donation programs—Mini review - Najdecki, Robert; Michos, Georgios; Peitsidis, Nikos; Timotheou, Evangelia; Chartomatsidou, Tatiana; Kakanis, Stelios; Chouliara, Foteini; Mamopoulos, Apostolos; Papanikolaou, Evangelos (Frontiers in Endocrinology, 2022)
Oocyte donation programs involve young and healthy women undergoing heavy ovarian stimulation protocols in order to yield good quality oocytes for their respective recipient couples. These stimulation cycles were for many years beset by a serious and potentially lethal complication known as Ovarian Hyperstimulation Syndrome (OHSS). The use of the short antagonist protocol is not only patient friendly but has also halved the need for hospitalization due to OHSS sequalae. Moreover, the replacement of b-HCG with GnRH-agonist triggering has reduced OHSS occurrence significantly, almost eliminating its moderate to severe presentations. Despite differences in the dosage and type of GnRH-a used across different studies, comparable number of mature oocytes retrieved, fertilization, blastulation and pregnancy rates in egg recipients are seen when compared to HCG triggered cycles. Nowadays, GnRH-a tend to be the triggering agent of choice in oocyte donation cycles as it is effective, safe and reduce OHSS incidence. However as GnRH-a triggering does not eliminate OHSS entirely, caution should be practiced in order to avoid unnecessary lengthy and heavy ovarian stimulation which could potentially compromise both donor’s wellbeing as well as treatment’s efficacy.